The Role of Civil Association in fostering Excellence and Creativity Creators for "A Homeland Foundation in Damascus as A model" - محمد, أسامة; معلا , فراس (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Talented and creative people represent a very important national wealth. It is the duty of society to study their needs, ways to develop and discover these needs, and motivate them for creativity and innovation; Be this interest from the state or from civil associations that care for talents and innovators, because high hopes are held on the talented and the superior to solve problems, maintain future outlooks, and develop ways of a decent life for their people. The current research aims to identify the role of civil associations in supporting the talented and creative in the Syrian Arab Republic by getting acquainted with the services provided by the Civil Society for Supporting the Talented and Creative, and identifying the domains of the talented and creative people that the Civil Society is interested in. This is done through conducting a field study on the reality of the work of the Creators for a Homeland Foundation to nurture talent and creativity. It also aimed to identify differences of statistical significance with reagrds to the role of NGOs in supporting the talented and creative, which are ascribed to the gender and educational qualification variables. The researcher has used the descriptive analytical method for its relevance to the nature of the research, and the original community of the research encompassed all members of the board of directors and workers in the Creators for a Homeland Foundation in the city of Damascus, amounting to (28) male and female workers in 2021. Furthermore, all the original community was taken as a sample for research, the questionnaire being used as a data collection tool, and the research results concluded: no difference of statistical significance between the average scores of the sample concerning the role of NGOs in supporting the talented and creative can be ascribed to the gender variable. The research also found that the differences between the arithmetic means of the sample’s answers on the axis of services provided by associations to the talented and creative and at the level of the questionnaire as a whole were between high schoolers or less degree holders and postgraduates, in favor of postgraduates with regards to the educational qualification variabl